THE EFFECT OF INVESTMENT DECISIONS, FINANCING DECISIONS, AND DIVIDEND POLICY ON FIRM VALUE IN THE FOOD AND BEVERAGE SUBSECTOR FOR THE 2019–2024 PERIOD - Hallie Nugroho Hardin; I Gst. Bgs. Wiksuana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to analyze the effect of investment decisions proxied by the Price Earnings Ratio (PER), financing decisions proxied by the Debt to Equity Ratio (DER), and dividend policy proxied by the Dividend Payout Ratio (DPR) on firm value, measured by Price to Book Value (PBV), in food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2019–2024 period. This research employs a quantitative approach with a sample of 20 companies selected through purposive sampling. Data analysis techniques include descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results indicate that investment decisions, financing decisions, and dividend policy have a significant effect on firm value.